Evaluación técnico-financiera del potencial del pozo exploratorio vino 1 del campo Cupiraco mediante pruebas de presión DST (2019)
The Cupiraco Field is currently producing hydrocarbons from the Formation Horses at 7900ft- 8000ft and some limestones between 8000ft - 8500ft, but in this one, Arena T, Arena U and Limestone Formations have never been evaluated (Limestones A1, A2 and A3) that are located at a greater depth. Once a geological and seismic study was carried out, it was found that these formations they are highly likely to contain hydrocarbons and should be evaluated for establish their properties and corresponding potentials. For these reasons, the Vino1 exploratory well was created in which the DST pressure tests at each training, where the results were evaluated at from the Horner method. Subsequently, laboratory tests were performed. PVT, rock and fluid characterizations, estimates of their reserves and finally their potentials were determined. This work was evaluated financially based on the Net Present Value indicator (VPN), which is the most suitable for projects that will have long-term profits term as is the case with this.